PENGENALAN KEPADA CALON LULUSAN AKUNTANSI TERHADAP PROSPEK KERJA DIMASA DEPAN - Radina Modjaningrat; Atik Isniawati; Sri Ari Wahyuningsih; Agustina Indriani; Ahmad Basid Hasibuan; jombrik; Saminem (Bajang Institute, 2022)
Abstract The purpose of this community service activity is to introduce prospective accounting graduates about the future job prospects of accountants and provide an understanding of the importance of the role of an accountant in business and government institutions. Therefore, this community service activity is expected to encourage prospective accounting graduates to improve their competencies. according to the needs of the world of work. The method used in this community service activity is lecturing with a sample audience of students of SMKN 44 Cempaka Baru Village, Kemayoran District with 212 class 12 student participants and divided into 12 classes. In this lecturing approach, the activity begins by conducting a pre-test to participants, namely SMKN 44 students to find out the extent of the participants' knowledge regarding the material to be delivered, followed by giving material using the lecturing method. Finally, a post-test was conducted to determine the extent to which the participants understood the material that had been presented. Comparison of the results of the pre-test and post-test showed an increase in the understanding of prospective accounting graduate students regarding accountants' future job prospects. Before lecturing, only 29.3% of students understood about accounting job prospects, while 70.7% did not understand. However, after lecturing students who understand accounting job prospects increased significantly, namely 98.3%, while those who did not understand only 1.7%. The contribution of this community service activity is felt by prospective accounting graduates by providing motivation to deepen accounting knowledge in order to improve their abilities and competencies in the world of